2012
DOI: 10.1371/journal.pone.0041024
|View full text |Cite
|
Sign up to set email alerts
|

Cell Elasticity Determines Macrophage Function

Abstract: Macrophages serve to maintain organ homeostasis in response to challenges from injury, inflammation, malignancy, particulate exposure, or infection. Until now, receptor ligation has been understood as being the central mechanism that regulates macrophage function. Using macrophages of different origins and species, we report that macrophage elasticity is a major determinant of innate macrophage function. Macrophage elasticity is modulated not only by classical biologic activators such as LPS and IFN-γ, but to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
226
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(249 citation statements)
references
References 46 publications
(77 reference statements)
13
226
2
Order By: Relevance
“…58 Recent research showed that the cell mechanical properties determined the macrophage functions. 59 Here the measured Young's modulus of macrophages was in the range of 1−3 kPa and became 2−5 kPa after the activation of phagocytosis, comparable to the measured values of the cell Young's modulus by other groups. In the era of personalized medicine, investigating the properties of patients at single-cell levels is increasingly important.…”
Section: Resultssupporting
confidence: 88%
“…58 Recent research showed that the cell mechanical properties determined the macrophage functions. 59 Here the measured Young's modulus of macrophages was in the range of 1−3 kPa and became 2−5 kPa after the activation of phagocytosis, comparable to the measured values of the cell Young's modulus by other groups. In the era of personalized medicine, investigating the properties of patients at single-cell levels is increasingly important.…”
Section: Resultssupporting
confidence: 88%
“…S6) has been reported in previous studies using magnetic twisting cytometry (58). This effect is not likely due to a low expression level of myosin IIA in macrophages (59,60).…”
Section: Discussionsupporting
confidence: 71%
“…Adhesion to a rigid (not soft) substrate for many cell types drives cell spreading with assembly of stress fibers and polarization of nonmuscle myosin-II 44,46,52,53 ; macrophages are certainly mechanosensitive in adhesion 45,54,55 and phagocytosis. 35 Target rigidity can therefore contribute to the generation of contractile forces during the phagocytosis of foreign cells.…”
Section: Resultsmentioning
confidence: 99%